Acquired hemophilia A in a patient with advanced prostate cancer - Daniel da Motta Girardi; Douglas Rafael Almeida Silva; Paula Ribeiro Villaça; Ciro Eduardo Souza; Leonardo Gomes da Fonseca; Diogo Assed Bastos; Paulo Marcelo Gehm Hoff (University of São Paulo, 2015)
Acquired hemophilia A (AHA) is a rare disorder that results from the presence of autoantibodies against the clotting factor VIII (FVIII) causing hemorrhagic disorders. This entity is mostly associated with autoimmune diseases, pregnancy, the postpartum period, drugs and malignancy. Among the solid cancers, prostate neoplasm is the most common cause of AHA. The management of AHA involves the control of active bleeding and the use of specific therapies to eliminate the inhibitor. The authors describe the case of an 87-year-old man with prostate cancer who developed a bleeding disorder 5 years after the cancer diagnosis. Treatment with prednisone did not reach a satisfactory clinical response, which was only achieved with the association of azathioprine. The patient became asymptomatic with no further bleeding episodes, but developed a fatal sepsis after 3 months of treatment with these immunosuppressive agents.